Positive Digital Leadership and Employee Well-Being in the Era of Remote Work - Stachewicz, Patrycja (Journal of Positive Management, 2026)
Purpose: This study focuses on the role of positive digital leadership in shaping employee well-being in the era of remote work. The research employs the theoretical frameworks of Positive Organizational Scholarship and the Job Demands-Resources model. The aim of the study is to provide a comprehensive assess of how remote work leaders support employee well-being, while simultaneously optimizing the utilization of work-related resources. Design/Methodology/Approach: The study was based on a qualitative methodology, utilizing semi-structured interviews with 30 employees working in remote or hybrid settings. The interpretation of the results was included in the Positive Organizational Scholarship and Job Demands-Resources models. Findings: The survey results indicate that positive digital leadership is one of the key factors influencing the well-being of employees working remotely or in a hybrid arrangement within Polish organisations. Leaders who foster relationships that encourage positive leadership behaviours improve employees’ well-being, which leads to reduced stress and increased productivity. Implications/limitations: The study highlighted the key role of leaders in fostering the well-being of remote workers. Managers should adopt positive leadership practices that support authentic leadership, employee potential and effective resource management. The cross-sectional nature of the study limits the scope for generalisations; therefore, future research should focus on long-term effects across different technological and cultural contexts Originality/value: This study uses the theoretical frameworks of Positive Organizational Scholarship and Job Demands-Resources in the context of remote and hybrid work in Poland. The study shows how positive digital leadership and effective use of work resources affect employee well-being. Keywords: Positive Organizational Scholarship, Job Demands-Rescources, remote work Paper type: Research Paper